RECEPTION OF F. NIETZSCHE’S IDEAS IN M. FOUCAULT’S GENEALOGICAL HERMENEUTICS: THE POSSIBILITY OF CRITIQUE OF HISTORY AND SOCIAL PRACTICES - Mickevičius, Arūnas (Problemos, 2017)
The aim of the paper is to explicate Foucault’s interpretational access to Nietzsche’s basic concepts; second, to show Nietzsche’s importance for the development of M. Foucault‘s genealogy; and third, to disclose how Foucault’s genealogical research in polemics with J. Habermas turns to the problem of legitimizing the question “How can genealogical history and a variety of social practices criticism?” This article is intended to support the thesis that genealogical research developed by Foucault can be seen as legitimate historical and social practice and an alternative to Habermasian project.
Keywords: incompleteness of interpretation; genealogy; hermeneutics; archeology; social criticism; power